2008
DOI: 10.1038/nmeth.f.230
|View full text |Cite
|
Sign up to set email alerts
|

AlphaLISA immunoassays: the no-wash alternative to ELISAs for research and drug discovery

Abstract: advertising feature an8 | December 2008 | nature methods application notes cell Biology biotinylated antibody bound to streptavidin-coated donor beads and a second antibody conjugated to AlphaLISA acceptor beads. The binding of the two antibodies to the analyte brings donor and acceptor beads into proximity. Laser irradiation of donor beads at 680 nm generates a flow of singlet oxygen, triggering a cascade of chemical events in nearby acceptor beads, which results in a chemiluminescent emission at 615 nm. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 6 publications
0
74
0
Order By: Relevance
“…Optimizing all assay components is important since stimulated lymphocytes can produce a myriad of diverse cytokines when activated and the type of cytokine markedly depends on the nature of the stimulating reagent as well as assay study conditions. 20 The authors evaluated a combination of four different mitogens, alone and in combination, over a range of concentrations with four incubation periods (24,48,72,96 hours) in cultured PBMCs. Upon completion of the studies and quantifying the cell stimulation index and levels of TNFα, it was concluded that the optimal conditions for induced cell proliferation were a medium supplemented with a mixture of PHA:Con A (at a concentration of 5 µg/ mL each) for an incubation period of 72 hours.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Optimizing all assay components is important since stimulated lymphocytes can produce a myriad of diverse cytokines when activated and the type of cytokine markedly depends on the nature of the stimulating reagent as well as assay study conditions. 20 The authors evaluated a combination of four different mitogens, alone and in combination, over a range of concentrations with four incubation periods (24,48,72,96 hours) in cultured PBMCs. Upon completion of the studies and quantifying the cell stimulation index and levels of TNFα, it was concluded that the optimal conditions for induced cell proliferation were a medium supplemented with a mixture of PHA:Con A (at a concentration of 5 µg/ mL each) for an incubation period of 72 hours.…”
mentioning
confidence: 99%
“…The AlphaLISA ® (Amplified Luminiscent Proximity Homogenous) immunoassay (PerkinElmer, Waltham, MA) is a bead-based assay that was developed from a diagnostic assay technology known as LOCI (Luminescent Oxygen Channeling Assay). 23,24 In this chemiluminescent assay, singlet oxygen molecules generated by high energy laser irradiation (at 680 nm) of donor beads excite acceptor beads. This results in a chemical cascade that yields an emission signal at 615 nm.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The development of highly sensitive enzyme substrates have led to ultrasensitive ELISAs and chemiluminescent immunoassays [9], while the use of superior fluorescent dyes improved the fluorescent immunoassays. Additionally, the use of infra-red dyes, quantum dots, gold nanoparticles, beads, and other nanomaterial/nanocomposites enabled the development of new ELISA formats, such as the naked-eye ELISA that was demonstrated using gold nanoparticles [10].The development of bead-based AlphaLISA by Perkin Elmer [11] is another major development in immunodiagnostics as it has critically reduced the immunoassay duration and complexity. It employs a streptavidin-coated Alpha donor bead and anti-analyte-conjugated AlphaLISA acceptor bead, which come into close proximity to generate the signal in the presence of analyte.…”
mentioning
confidence: 99%